Set it and forget it? Financing retirement in an age of defaults - Goodman, Lucas; Mukherjee, Anita; Ramnath, Shanthi (Journal of Financial Economics, 2023)
Retirement savings abandonment is a rising concern connected to defined contribution systems and default enrollment. We use tax data on Individual Retirement Accounts (IRAs) to establish that for a recent cohort, 0.4% of retirement-age individuals abandoned an aggregate of $66 million, proxied by a failure to claim over ten years after a legal requirement to do so. Analysis of state unclaimed property databases suggests that workplace defined contribution plans are abandoned at a higher rate than IRAs. Finally, regression discontinuity estimates show that certain accounts created by default enrollment are at higher risk of abandonment by passive savers.